Role of LncMALAT1-miR-141-3p/200a-3p-NRXN1 Axis in the Impairment of Learning and Memory Capacity in ADHD - Mu, Y; Li, J; Zhang, S; Zhong, F; Zhang, X; Song, J; Yuan, H; Tian, T; Hu, Y (Physiological research, 2023)
As a prevalent neurodevelopmental disease, attention-deficit hyperactivity disorder (ADHD) impairs the learning and memory capacity, and so far, there has been no available treatment option for long-term efficacy. Alterations in gene regulation and synapse-related proteins influence learning and memory capacity; nevertheless, the regulatory mechanism of synapse-related protein synthesis is still unclear in ADHD. LncRNAs have been found participating in regulating genes in multiple disorders. For instance, lncRNA Metastasis Associated Lung Adenocarcinoma Transcript 1 (MALAT1) has an essential regulatory function in numerous psychiatric diseases. However, how MALAT1 influences synapse-related protein synthesis in ADHD remains largely unknown. Here, our study found that MALAT1 decreased in the hippocampus tissue of spontaneously hypertensive rats (SHRs) compared to the standard controls, Wistar Kyoto (WKY) rats. Subsequent experiments revealed that MALAT1 enhanced the expression of neurexin 1 (NRXN1), which promoted the synapse-related genes (SYN1, PSD95, and GAP43) expression. Then, the bioinformatic analyses predicted that miR-141-3p and miR-200a-3p, microRNAs belonging to miR-200 family and sharing same seed sequence, could interact with MALAT1 and NRXN1 mRNA, which were further confirmed by luciferase report assays. Finally, rescue experiments indicated that MALAT1 influenced the expression of NRXN1 by sponging miR-141-3p/200a-3p. All data verified our hypothesis that MALAT1 regulated synapse-related proteins (SYN1, PSD95, and GAP43) through the MALAT1-miR-141-3p/200a-3p-NRXN1 axis in ADHD. Our research underscored a novel role of MALAT1 in the pathogenesis of impaired learning and memory capacity in ADHD and may shed more light on developing diagnostic biomarkers and more effective therapeutic interventions for individuals with ADHD.
Keywords: Rats, Inbred WKY; MicroRNAs; RNA dlouhá nekódující; Rats; krysa rodu Rattus; Animals; Attention Deficit Disorder with Hyperactivity; RNA, Long Noncoding; potkani inbrední WKY; regulace genové exprese; Gene Expression Regulation; hyperkinetická porucha; zvířata; mikro RNA